Implementasi E-Marketing Dan Etika Bisnis Untuk Meningkatkan Volume Penjualan Bagi Pelaku UMKM Di Masa Pandemi Covid-19 - Masni, Masni; Saleh, Hamsir (Universitas Gorontalo, 2022)
This study was conducted to determine how much influence the implementation of E-Marketing and business ethics has on increasing the sales volume of MSMEs in Boalemo Regency by using the variables of E-Marketing and Business Ethics as independent variables and Sales Volume as the dependent variable. This study uses quantitative methods with multiple linear regression analysis techniques with the help of SPSS software version 24 with a sample of 100 SMEs as respondents. The results of the study indicate that there is a significant influence between the implementation of E-Marketing and Business Ethics on the Sales Volume of MSMEs.